Rancang Bangun Aplikasi Ealah E- Learning Pengenalan Perograman Dasar Berbasiss Web Dengan Menggunakan Algoritma Edit Distance Pada Koreksi Otomatis Jawaban Essay - Firmanda Himawan, Ahmad; Dwi Nuryana, I Kadek; Ali, Mahrus (Inovate, 2021)
E-learning is an innovative learning medium that must be optimized, so that education delivery will continue to develop. By using E-learning, the problems of space and time that have been an obstacle in learning are no longer a barrier. Apart from that, the existence of e-learning which has the feature of being able to correct essay answers automatically is felt to be able to help teachers to provide grades to students, and students can learn independently and can get more learning material and can communicate with teachers outside the classroom. In this research the USDP (unified software development process) method, Edit Distance algorithm, and Cosine Simmiliarity are used to match the students' answers with the teacher's answer key, the counting process starts from Text prepocessing, Case floading, filtering, and tokenizing, then processing of Edit Distance and Cosine Simmiliarity. The results of this study are in the form of a web-based e-learning application which is expected to help learning, especially for teachers, to make it easy to give grades to students in exams or essay assignments. In the tests conducted by the author with data from 5 essay questions along with the answer keys and student answer data, and the authors conducted 2 application tests using the same data by applying the edit distance algorithm the value = 94.98 while without the edit distance algorithm it got a value of = 78, 04 and the difference in value = 16.94 from the total value = 100. Keywords: E-learning, USDP, unified software development process, Cosine Simmiliarity, Edit Distance, Levenstein Distance, Essay Automatic Correction.